Evaluating the Psychometric Properties of the Persian Self-Management Scale for Kidney Transplant Recipients - Khezerloo, Somayeh; Mahmoudi, Hosein; Vafadar, Zohreh (Urology Journal, 2019)
Purpose: There was no appropriate instrument for assessing the self-management of Iranian kidney transplant recipients. This study was done to translate the Self-Management Scale for Kidney Transplant Recipients into Persian and evaluate its psychometric properties. Material and Methods: This cross-sectional methodological study was done from October 2016 to March 2017. The psychometric properties of the scale were evaluated in the following four steps: forward-backward translation, face and content validity assessments, construct validity assessment via exploratory factor analysis, and reliability assessment via internal consistency and test-retest techniques. Results: The means of item impact score, content validity ratio, and simplicity, clarity, and relevance content validity indices were 3.94, 0.73, 0.96, 0.93, and 0.98, respectively. Exploratory factor analysis revealed a four-factor structure for the scale which explained 70.75% of the total self-management variance. The four factors of the scale were “self-monitoring”, “self-care behaviors”, “early detecting and coping with abnormalities”, and “drug management”. The Cronbach’s alpha and the test-retest intraclass correlation coefficient of the scale were 0.73 and 0.90, respectively. Conclusion: The Persian Self-Management Scale for Kidney Transplant Recipients has acceptable validity and reliability. It can be used in educational and clinical environments and also in research studies for measuring kidney transplant recipients’ self-management.